A Sulfur Heterocyclic Quinone Cathode Towards High‐Rate and Long‐Cycle Aqueous Zn‐Organic Batteries - Sun, Qi‐Qi; Sun, Tao; Du, Jia‐Yi; Li, Kai; Xie, Hai‐Ming; Huang, Gang; Zhang, Xin‐Bo (Advanced materials (Weinheim), 2023)
Organic materials have attracted much attention in aqueous zinc‐ion batteries (AZIBs) due to their sustainability and structure‐designable, but their further development is hindered by the high solubility, poor conductivity, and low utilization of active groups, resulting in poor cycling stability, terrible rate capability, and low capacity. In order to solve these three major obstacles, a novel organic host, benzo[b]naphtho[2’,3’:5,6][1,4]dithiino[2,3‐i]thianthrene‐5,7,9,14,16,18‐hexone (BNDTH), with abundant electroactive groups and stable extended π‐conjugated structure is synthesized and composited with reduced graphene oxide (RGO) through a solvent exchange composition method to act as the cathode material for AZIBs. The well‐designed BNDTH/RGO composite exhibits a high capacity of 296 mAh g−1 (nearly a full utilization of the active groups), superior rate capability of 120 mAh g−1, and a long lifetime of 58 000 cycles with a capacity retention of 65% at 10 A g−1. Such excellent performance can be attributed to the ingenious structural design of the active molecule, as well as the unique solvent exchange composition strategy that enables effective dispersion of excess charge on the active molecule during discharge/charge process. This work provides important insights for the rational design of organic cathode materials and has significant guidance for realizing ideal high performance in AZIBs. A fully composited benzo[b]naphtho[2',3':5,6][1,4]dithiino[2,3‐i]thianthrene‐5,7,9,14,16,18‐hexone/reduced graphene oxide (BNDTH/RGO) is designed to simultaneously conquer the low utilization of active sites, intrinsic poor conductivity, and strong solubility of organic electrode materials, realizing the construction of Zn‐organic batteries with record‐high cycling stability. This work brings new opportunities for the exploration of ultra‐stable organic cathode materials for Zn‐ion batteries.